Secure Programming Cookbook for C and C++ - Messier, Matt (O'Reilly, 2011)
Secure Programming Cookbook for C and C++ is an important new resource for developers serious about writing secure code for Unix® (including Linux®) and Windows® environments. This essential code companion covers a wide range of topics, including safe initialization, access control, input validation, symmetric and public key cryptography, cryptographic hashes and MACs, authentication and key exchange, PKI, random numbers, and anti-tampering.